IMPLEMENTASI PERATURAN BUPATI NOMOR 14 TAHUN 2016 TENTANG PEMBENTUKAN, SUSUNAN ORGANISASI DAN TATA KERJA UNIT PELAKSANA TEKNIS PADA PROGRAM PAKET C DI SANGGAR KEGIATAN BELAJAR KABUPATEN PONOROGO - Suliyani, Siti (Master of Public Administration, Universitas Slamet Riyadi, 2020)
Based on the results of research and discussion, a conclusion can be drawn thatcommunication, namely reviewing the Permendikbud and juxtaposing with theRegent's Regulation regarding the establishment of the Ponorogo SKT UPT(Perbup No. 51/2008 concerning the formation, organizational structure andworking procedures of the Technical Implementation Unit within the EducationOffice of Ponorogo Regency ). Ponorogo SKB Resources have completed theirorganizational structure based on the Director General of Early ChildhoodPendidian and Community Education Ministry of Education and Culture No.1453 Year 2016. Disposition, All Steak Holders in the government are expected tounderstand the operational guidelines and technical guidelines for implementingthe Package C equality program so that in its implementation not experiencesignificant obstacles. If this is not done then the marginal people who have beenorganized and who have learned will experience a second failure. Consideringthat the average citizen learning that has been accommodated in the C Packageequality program are those who have failed in taking formal education, due toconstraints on costs, time and conditions. Organizational Structure, HR availableat SKB Ponorogo in addition to having educational qualifications relevant to thefield of study in which they are expected to master a variety of skills competenciesfor example computer competence, delivery, catering, fashion and bridal makeup.